Assessing the impact of agri-environmental schemes on the eco-efficiency of rain-fed agriculture - Beltrán-Esteve, M.; Gómez-Limón, J. A.; Picazo-Tadeo, A. J. (Spanish Journal of Agricultural Research, 2012)
This paper analyses the impact of the Agri-environmental Extensification Scheme for the Protection of Flora and Fauna (F&F Scheme) on the eco-efficiency of a sample of dryland farms in the Spanish region of Castile and Leon. Using Data Envelopment Analysis (DEA) and the so-called program decomposition approach to efficiency measurement, we explore whether or not the production technology of the farms included in the F&F Scheme is more eco-efficient than the technology used by farms that are not included in the Scheme. The re-sults obtained confirm the foregoing hypothesis, providing evidence that environmental pres-sures could be reduced if all farms adopted the F&F Scheme technology. Furthermore, shad-ow prices are used to assess the monetary value of the potential reduction in environmental pressures that farms could achieve by adopting the F&F Scheme. The results show that the average opportunity cost of the decrease in environmental pressures (€55.65 ha-1) is similar to the compensation received by farms included in the F&F Scheme. Nevertheless, bearing in mind the great diversity of farms, we recommend agricultural policymakers to use an auction system to award such environmental contracts.